Dinamika dan faktor penentu dalam perkembangan kurikulum pendidikan - Alkhuzaiyah, Ma’bad; Muhammad, Faris Syaifuddin; Muludya, Dita; Sutiah, Sutiah (Maliki Interdisciplinary Journal, 2024)
The development of the educational curriculum is a dynamic process that is influenced by various factors. This article examines the dynamics and determining factors in the development of the educational curriculum. These dynamics include social and cultural changes, technological advances, economic needs, as well as government and political policies. Determining factors that play an important role include national education goals, community needs and expectations, educational research and innovation, standards and evaluation, and availability of resources. Understanding and managing these factors is important to produce a curriculum that is relevant, adaptive, and able to prepare the younger generation to face future challenges.